2010
DOI: 10.4314/eamj.v86i6.54138
|View full text |Cite
|
Sign up to set email alerts
|

Intestical polyparasitism in a rural Kenyan community

Abstract: Background: Polyparasitism seems to be a common feature in human populations in sub-Saharan Africa. However, very little is known about its epidemiological significance, its long term impact on human health or the types of interactions that occur between the different parasite species involved. Objectives: To determine the prevalence and co-occurrence of intestinal parasites in a rural community in the Kibwezi, Makueni district, Kenya. Design: A cross sectional study. Setting: Kiteng'ei village, Kibwezi, Makue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
6
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 14 publications
5
6
0
Order By: Relevance
“…Previous study [12] had reported poor hygienic practice in a similar study in Oju Local Government Area of Benue State. However, the prevalence of polyparasitism in the study area was low and it was in agreement with [12] who reported a low prevalence in Oju of Benue State but differs with that of Nguhiu, et al [13] in 2014 in Kenya who reported polyparasitism rate of 71.4%. The females had higher prevalence than the males, this could be as a result of the domestic roles (cooking, laundry, cleaning up the children after defecation) women play in a household which could pre-expose them to the infective stages of the various parasites.…”
Section: Discussionsupporting
confidence: 89%
“…Previous study [12] had reported poor hygienic practice in a similar study in Oju Local Government Area of Benue State. However, the prevalence of polyparasitism in the study area was low and it was in agreement with [12] who reported a low prevalence in Oju of Benue State but differs with that of Nguhiu, et al [13] in 2014 in Kenya who reported polyparasitism rate of 71.4%. The females had higher prevalence than the males, this could be as a result of the domestic roles (cooking, laundry, cleaning up the children after defecation) women play in a household which could pre-expose them to the infective stages of the various parasites.…”
Section: Discussionsupporting
confidence: 89%
“…Prevalence and distribution of gastro intestinal protozoa Out of a total of 120 screened stool samples, 34 (28.3%) tested positive for gastrointestinal protozoans with Entamoeba histolytica, Giardia lamblia or both (co-infections) accounting for 18.0 %, 5.0 % and 5.0 % respectively. This prevalence is higher than Kitui County, that reported a prevalence 12.6%, of intestinal protozoa (Nguhiu et al, 2009). The high rates observed were comparable to other ndings in Mukuru informal settlement in Nairobi with 25.6%, (Mbae et al, (2013).…”
Section: Discussionsupporting
confidence: 76%
“…This indicated very unsanitary habits especially in source of drinking water and the type of toilet system use. This study shows that prevalence of polyparasitism is lower compared to that of in 2014 in Kenya [12,13,14] who reported polyparasitism rate of 71.4%, 22%. The present study is not in agreement with the previous studies.…”
Section: Resultsmentioning
confidence: 69%